Political unionism and the ethical question of trade union involvement in government : historical and conceptual issues and analysis of the problem : a case study on COSATU - Cedras, Jody Paul (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Phil.) -- University of Stellenbosch, 1998.